Believing when credible: Talking about future plans and past actions - Péter Vida (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
We explore in an equilibrium framework whether games with multiple Nash equilibria are easier to play when players can communicate. We consider two variants, modelling talk about future plans and talk about past actions. The language from which messages are chosen is endogenous, messages are allowed to be vague. We focus on equilibria where messages are believed whenever possible, thereby develop a theory of credible communication. Predictions confirm the longstanding intuition for Aumann's (1990) Stag Hunt game which applies directly to an investment game with positive spillovers. Our results shed new light on the multiplicity of equilibria in economic applications.
urn:nbn:de:bvb:19-epub-25291-5
Keywords: C72; D83; 330; Pre-Play Communication; Cheap Talk; Credibility; Coordination; Language; Multiple Equilibria